Adaptive Learning to Develop and Apply to Arabic Language Learning in Higher Education - Jill, Oller; Gilkerson, Griebel; Jane, Dale; Hannon, Bowman; Steven, Hyunjoo (Al-Hijr: Journal of Adulearn World, 2023)
Lately, many have been found in the implementation of learning processes using various methods. This can be seen by the number of learners that uses technology-based media that can improve and support the learning process in a university. The learning process is one of the most important things in the world of education. Education is said to be of high quality if, in the learning process, it can improve and develop the talents and skills that exist in students. The purpose of this study was to determine the learning process using Adaptive Learning in developing Arabic learning in universities. The method in this study uses quantitative research methods. The data obtained is through the distribution of questionnaires containing statements in them. The distribution of the questionnaire is by utilizing the Google Form application. The results of this study explain that the learning process using Adaptive Learning can develop students' Arabic learning in universities. This study concludes that the learning process by utilizing Adaptive Learning to develop Arabic learning in higher education is very suitable to be applied in the learning process. The limitation of this study is that researchers only conduct this research at the university level which requires a learning process that suits the needs of students, one of which is by utilizing this Adaptive Learning. Researchers hope that the next researcher can develop the Arabic learning process at a more advanced stage. This study also recommends to future researchers make this research a reference in conducting research related to the learning process using Adaptive Learning.